2020
DOI: 10.3892/mco.2020.2051
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of SOX2 expression in small‑cell neuroendocrine carcinoma of the endometrium

Abstract: Small-cell neuroendocrine carcinoma (NEC) of the endometrium is an extremely rare and highly aggressive carcinoma. Sex-determining region Y-box 2 (SOX2) is a master transcription factor regulating the self-renewal, maintenance of stem cell properties and pluripotency of embryonic stem cells, and recent studies revealed that SOX2 plays important roles in cancer growth and progression in several types of carcinomas, including small-cell neuroendocrine carcinoma (NEC) of the lung and oesophagus. Few studies to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Overexpression of SOX2 has been detected in human cancers, and therefore, it may serve as an oncogene [ 28 ]. Additionally, previous studies have examined the effect of SOX2 levels on small cell neuroendocrine carcinomas (NECs) in certain organs, and found that SOX2 possibly plays a vital role in small cell NEC progression in the endometrium, esophagus, and lung [ 29 31 ]. Nonetheless, little research has focused on SOX2 expression and its clinical value in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of SOX2 has been detected in human cancers, and therefore, it may serve as an oncogene [ 28 ]. Additionally, previous studies have examined the effect of SOX2 levels on small cell neuroendocrine carcinomas (NECs) in certain organs, and found that SOX2 possibly plays a vital role in small cell NEC progression in the endometrium, esophagus, and lung [ 29 31 ]. Nonetheless, little research has focused on SOX2 expression and its clinical value in cancer.…”
Section: Discussionmentioning
confidence: 99%